Phytophthora Management in Citrus Nurseries - Megan M. Dewdney; Jamie D. Burrow (EDIS)
This 2-page fact sheet is a minor revision written by Megan M. Dewdney and Jamie D. Burrow, and published by the Plant Pathology Department, July 2019.